The effect of financial technology (Fin-tech) on the conventional banking industry in India - Chouhan, Vineet; Ali, Sajid; Sharma, Raj Bahadur; Sharma, Anjali (International Journal of Innovative Research and Scientific Studies, 2023)
The purpose of the study is to measure the impact of financial technology on the banking industry. Digital disruption has an impact on bank business models as well as conventional businesses as a result of changed customer behavior. This paper examines the impact of financial technology on the Indian conventional banking industry using a structured questionnaire filled out by 300 customers’ of a bank selected using simple random sampling. For hypothesis testing, the statistical technique of regression analysis is used.In order to identify the impact of financial technology on the banking industry, the value propositions that influence the adoption of financial technology or banking products are analysed using importance and usefulness criteria such as customer satisfaction, net promotion score, promotion, ease of use, etc. The results show that banks have been positively impacted by the use of financial technology as it can now enhance their value proposition which includes improved service quality, marketing and a wide range of merchants. The research has implications for the banking industry that can make the services easily accessible for customers and improve their value proposition. Furthermore, customers are aware that the banking industry uses financial technology which can make their work easier too. The literature in the field of financial technology is limited in terms of theory and the practical issues are being improved with easy adoption and proper marketing needs in the research. This will improve and guide future research in the same area.